The Rebooting in Sports and Physical Activities After COVID-19 Italian Lockdown: An Exploratory Study - Guicciardi, Marco; Pazzona, Riccardo (Frontiers in Psychology, 2020)
The lockdown imposed in Italy to reduce the spread of COVID-19 posited unusual challenges to people practicing sports and physical activities. The rebooting of activities highlighted the need to cope with new behaviors and routines, as wearing a face mask while exercising. We conducted a web-based survey in Italy at the start of physical activities' rebooting, to investigate how people reacted to the new norms. Participants completed the questionnaires assessing insomnia, regulatory self-efficacy, optimism, mood states and mental toughness. Age, gender and environment were assumed as design variables. Results show that in outdoor activities, younger females compared to older manifest less regulatory self-efficacy, while younger male manifest more regulatory self-efficacy than older. In indoor activities, the reversed pattern of regulatory-self-efficacy was observed. Regarding to life orientation younger participants show less optimism and positive expectation for the future and seem to be more exposed to the unexpected effects of the restrictions: they showed more sleep disturbances, confusion, depression, anger and fatigue and less vigor and mental toughness than older. An understanding of the psychological implications of the rebooting phase can support the enactment of more appropriate behaviors to practice sports and physical activities when living at the time of Coronavirus.